Comparative Study on Nutritive Composition of Pawpaw (Carica papaya) and Black Plum (Syzygium cumini) Seed Flours - Adebayo E. Adeleke; Abel P. Onifade; Omotola E. Ishola; I. M. Olanipekun; Deborah F. Bamisaye (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2023)
This study investigated the chemical, minerals and nutritional composition of Pawpaw (C. Papaya) and black plum (S. Cumini) seed flours. The proximate composition was evaluated according to AOA C. The C. Papaya and S. Cumini seed flours were found to have moisture contents of 7.333±1.155, 6.666±2.309, Ash, 5.593±0.095, 5.717±0.126 Protein, 24.600±0.100, 22.36±0.493, Fat, 30.000±2.600, 26.233±0.451, Crude fibre 0.312±0.002, 0.031±0.001 and carbohydrates 32.590±1.155, 39.167±1.40%. Carbohydrates were the major nutrients found in C.Papaya 32.590±1.155% and S.Cumini seed 39.167±1.40. The minor components were crude fibre for both flours. The mineral composition was K, 0.022±0.001, 0.090±0.010, Ca, 0.046±0.006, 0.089±0.011, Zn, 0.078±0.002, 1.198±0.005, Fe, 0.435±0.325, 0.090±0.010, P, 0.116±0001, 0.067±0.007, 0.787±0.001, Mg, 2.322±0.077, 0.093±0.005 and Cu, 0.127±0.0255, 0.076±0.010 for C. Papaya and S. Cumini seed. C. Papaya seed contained a higher amount of Fe, P, Mg and Cu than S. Cumini seed .S. cumin seed flour was found to have a considerable amount of K, Zn and Ca than C, Papaya seed. The Amino acid profile for C.Papaya and S.Cumini were: Threonine, 1.134±0.002, 0.138±0.002, Histidine, 0.157±0.002, 0.257±0.002, Leucine, 0.416±0.002, 0.476±0.002, Isoleucine, 0.541±0.001, 0.641±0.001, Arginine, 0.887±0.001, 0.787±0.001, Methionine, 862±0.001, 0.181±0.001, Tryptophan, 0.013±0.001, 0.313±0.001, Tyrosine, 0.013±0.001, 1.113±0.001 and Aspartic acid, 0.731±0.002, 0.422±0.002 etc. Methionine was the most abundant acid in C. Papaya, while tyrosine was found in S. cumin seed. The least abundant acids were tryptophan and threonine for C. Papaya and S. Cumini seed. This suggested that the flour might serve as a rich source of essential protein. The flours possessed good functional properties and could serve as additives in baby food.